IMPLEMENTASI METODE TEAM ASSISTED INDIVIDUALIZATION (TAI) DALAM PEMBELAJARAN MENULIS TEKS EKSPLANASI DI SEKOLAH DASAR - Kristina Rita Ade Sarvita; Siti Halidjah; Rio Pranata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of students' explanatory text writing skills is reflected in the dominance of scores below 78 in student learning outcomes. This study aims to describe the implementation of the Team Assisted Individualization (TAI) method in teaching explanatory text writing at SDN 31 Pontianak Tenggara. This study uses a descriptive method with a qualitative approach. Data collection techniques consist of interviews and observations. The results of the survey indicate that implementing the TAI method in teaching explanatory text writing at SDN 31 Pontianak Tenggara can increase student involvement in explanatory text writing activities. Additionally, the TAI method can foster individual responsibility and encourage effective teamwork. This is proven by the fact that students are better able to analyze texts, utilize causal and chronological conjunctions appropriately, and produce more coherent writing. Therefore, the use of the TAI method in teaching explanatory texts has been proven to have a positive impact on improving students' writing skills at SDN 31 Pontianak Tenggara.